The privacy of customs records in Algerian law - Saiah, Zakia; Yesaad, Fadila (Journal of Human Sciences, 2022)
In view of the particular nature of customs offences and their extreme seriousness for the State and its economy, and the technical nature of such offences, the legislator has attached great importance to these reports. This is particularly important, both in terms of liberalization and in terms of strength of proof. This is confirmed by Executive Decree No. 301/18, which contains the specific form of customs records and the precise conditions for their validity, under the penalty of invalidity. In this study, we have relied on the descriptive and analytical approach to address the problem of the specificity of customs records in evidence.